Aplikasi Arang Aktif Tempurung Saboak (Borassus Flabellifer L) Sebagai Komponen Media Tumbuh Tanaman Gude (Cajanus Cajan L.) - Daud E. Adu; Merpiseldin Nitsae; Hartini R.L Solle (Universitas Medan Area, 2021)
Application of activated charcoal in agriculture will give advantage for plant growth because will enrich nutrients, mantain soil properties, enhance root development and increase microorganism propagation and activities that would support the plant growth. The objective of this research is to examine the effect of Saboak shell (Borassus flabellifer L.) activated charcoal addition into culture medium on growth of Gude plants (Cajanus cajan L.). Saboak shell (Borassus flabellifer L.) was carbonised in drum kiln to produce charcoal, then activated charcoal using H2SO4 for 180 minutes at 110 0C. The activated charcoal produced is then applied as a component of growing media of Gude plants (Cajanus cajan L) with levels of 5, 10 and 15% of the media weight. The results showed that addition of activated charcoal to the growth media could significantly increase the growth rate, growth rate and root length when compared to the control. The best addition of activated charcoal for Gude growth media is 10%, which with this level can increase growth height of 27.33 cm growth rate of 0.79 cm / day and root length of 15.13 cm for 30 days.